(untitled) (Homoeopathy for All, 2024)
Hair is crucial in shaping human self-image and personal identity. It’s one of the minority of physical characteristics that can be readily changed and controlled in accordance with cultural standards and fashion fads. Alopecia, often known as hair loss, is a prevalent issue that impacts millions of individuals. Although alopecia areata may occur at any age, the majority of people get the disorder early in life. More than 80% exhibit indications of the disease before the age of 40, with 40% experiencing symptoms by the age of 20. According to research, women are more prone than males to acquire alopecia areata, and certain races and ethnicities may be more susceptible to the disorder. It is essential to understand the intricate structure of hair, particularly when addressing the most prevalent causes of alopecia. The normal hair growth cycle can be disrupted and result in hair loss due to factors such as stress, hormonal imbalances, nutritional deficiencies, and genetic predispositions. Hair performs fundamental roles like thermoregulation, friction reduction, sun protection, and sensory organ function. Traditionally, hair on the head was considered a defensive shield and is still considered a prime symbol of personal identity. Yet, a range of hair-related problems including alopecia, insufficient hair growth, early graying, dandruff, thinning, and lack of shine are typical worries. The variety of features of hair, including its form, length, diameter, texture, and colour, along with the structure of its cross section, might impact the curl of the hair.